Evaluation of noise regression techniques in resting-state fMRI studies using data of 434 older adults - Scheel, Norman; Keller, Jeffrey N.; Binder, Ellen F.; Vidoni, Eric D.; Burns, Jeffrey M.; Thomas, Binu P.; Stowe, Ann M.; Hynan, Linda S.; Kerwin, Diana R.; Vongpatanasin, Wanpen; Rossetti, Heidi; Cullum, C. Munro; et al. (Frontiers in Neuroscience, 2022)
Subject motion is a well-known confound in resting-state functional MRI (rs-fMRI) and the analysis of functional connectivity. Consequently, several clean-up strategies have been established to minimize the impact of subject motion. Physiological signals in response to cardiac activity and respiration are also known to alter the apparent rs-fMRI connectivity. Comprehensive comparisons of common noise regression techniques showed that the “Independent Component Analysis based strategy for Automatic Removal of Motion Artifacts” (ICA-AROMA) was a preferred preprocessing technique for teenagers and adults. However, motion and physiological noise characteristics may differ substantially for older adults. Here, we present a comprehensive comparison of noise-regression techniques for older adults from a large multi-site clinical trial of exercise and intensive pharmacological vascular risk factor reduction. The Risk Reduction for Alzheimer’s Disease (rrAD) trial included hypertensive older adults (60-84 years old) at elevated risk of developing Alzheimer’s Disease (AD). We compared the performance of censoring, censoring combined with global signal regression, non-aggressive and aggressive ICA-AROMA, as well as the Spatially Organized Component Klassifikator (SOCK) on the rs-fMRI baseline scans from 434 rrAD subjects. All techniques were rated based on network reproducibility, network identifiability, edge activity, spatial smoothness, and loss of temporal degrees of freedom. We found that non-aggressive ICA-AROMA did not perform as well as the other four techniques, which performed acceptable with marginal differences, demonstrating the validity of these techniques. Considering reproducibility as the most important factor for longitudinal studies, given low false-positive rates and a better preserved, more cohesive temporal structure, currently aggressive ICA-AROMA is likely the most suitable noise regression technique for rs-fMRI studies of older adults.